ANALYSIS OF COMMERCIAL ADVERTISING AND BRAND ENGAGEMENT ON PURCHASE DECISIONS WITH INFLUENCERS AS AN INTERVENING VARIABLE AT PT. NUTRIFOOD INDONESIA - Munawar Rizal; Mesra B; Elfitra Desy Surya (RADJA PUBLIKA, 2025)
This study aims to determine the effect of commercial advertising, brand engagement, and influencer credibility on consumer purchase decisions at PT. Nutrifood Indonesia. The growing phenomenon of digital marketing has made the role of advertising media and influencers increasingly important in shaping consumer perception and decisions. This research employs a quantitative approach with a survey method, where data was collected through questionnaires distributed to Nutrifood consumers. The data analysis technique used is multiple linear regression. The results show that both partially and simultaneously, commercial advertising, brand engagement, and influencer credibility have a positive and significant effect on purchase decisions. Attractive advertisements, consumer involvement with the brand, and trust in influencers are proven to be important factors in encouraging the intention and decision to purchase Nutrifood products. These findings have strategic implications for companies in designing more effective marketing communications.